Utility of remnant liver volume for predicting posthepatectomy liver failure after hepatectomy with extrahepatic bile duct resection. Issue 1 (15th February 2021) - Yamamoto, R; Sugiura, T; Okamura, Y; Ito, T; Yamamoto, Y; Ashida, R; Ohgi, K; Otsuka, S; Uesaka, K
Abstract: Background: Hepatectomy with extrahepatic bile duct resection is associated with a high risk of posthepatectomy liver failure (PHLF). However, the utility of the remnant liver volume (RLV) in cholangiocarcinoma has not been studied intensively. Methods: Patients who underwent major hepatectomy with extrahepatic bile duct resection between 2002 and 2018 were reviewed. The RLV was divided by body surface area (BSA) to normalize individual physical differences. Risk factors for clinically relevant PHLF were evaluated with special reference to the RLV/BSA. Results: A total of 289 patients were included. The optimal cut-off value for RLV/BSA was determined to be 300 ml/m 2 . Thirty-two patients (11.1 per cent) developed PHLF. PHLF was more frequent in patients with an RLV/BSA below 300 ml/m 2 than in those with a value of 300 ml/m 2 or greater: 19 of 87 (22 per cent) versus 13 of 202 (6.4 per cent) ( P < 0.001). In multivariable analysis, RLV/BSA below 300 ml/m 2 ( P = 0.013), future liver remnant plasma clearance rate of indocyanine green less than 0.075 ( P = 0.031), and serum albumin level below 3.5 g/dl ( P = 0.015) were identified as independent risk factors for PHLF. Based on these risk factors, patients were classified into three subgroups with low (no factors), moderate (1–2 factors), and high (3 factors) risk of PHLF, with PHLF rates of 1.8, 14.8 and 63 per cent respectively ( P < 0.001). Conclusion: An RLV/BSA of 300 ml/m 2 is a simple predictor of PHLF in patients undergoing hepatectomy with extrahepatic bile duct resection. Abstract : The present study showed the importance of considering remnant liver volume (RLV)/body surface area (BSA) in addition to indocyanine green test for hepatectomy with extrahepatic bile duct resection. An RLV/BSA of 300 ml/m 2 is a simple and useful cut-off value for predicting posthepatectomy liver failure in patients undergoing major hepatectomy for cholangiocarcinoma.